Estudo fitoquímico, biológico e de atividades antioxidante e inibitória da acetilcolinesterase de Salacia crassifolia e Maytenus imbricata - Vanessa Gregório Rodrigues (2015)
In this work is presented the phytochemical study of the hexane (EHS), chloroform (ECS), ethyl acetate (EAS), and ethanolic (EES) extracts from leaves of Salacia crassifolia, and of the ethyl acetate extract (FSEAT) from roots of Maytenus imbricata, as well as the evaluation of the biological and antioxidant activity from these extracts and the isolated substances. The phytochemical study of S. crassifolia leds to the isolation and characterization of ten pentacyclic triterpenes (TTPCs), four flavonoids, two steroids, and other five compounds. Only one flavonoid was obtained from the ethyl acetate extract of M. imbricata. The isolated substances and mixtures had their structures elucidated by spectrometric methods (IR,1H and 13C NMR and mass). Attempts were made to obtain supramolecular complexes of the TTPCs and flavonoids with the -ciclodextrin, in the pursuit for promising drugs with higher bioavailability and water solubility. In order to achieve that, three different conditions, varying the reactants and solvents proportions, were utilized. All the extracts and some substances of S. crassifolia and M. imbricata were tested for the inhibitory acitivity of the acetylcholinesterase enzyme. The samples were actives, except by the steroid 3-O- -D-glucosil- -sitosterol. This result presents a perspective for more precise tests to prove the activity from these samples against Alzheimers disease. The extracts and some substances of S. crassifolia were tested against Salmonella typhimurium, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Streptococcus sanguinis, and Candida albicans. Two triterpenes and all extracts presented antimicrobial activity. The ethyl acetate (FSEAT) and methanolic (SEM) extract from M. imbricata, and the ethyl acetate (EAS) and ethanolic (EES) extract from S. crassifolia, as well as the flavonoids isolated from these extracts, were submitted to the antioxidant test. All extracts and substances presented high activity in DPPH tests. The hexane/ethyl ether extract (1:1) (SEH) from roots of M. imbricata and the major compound from this extract, tingenone, presented antiparasitc activity against Entamoeba histolytica, Giardia lamblia e Trichomonas vaginalis. The hexane/ethyl ether (1:1) (FSEH), ethyl acetate (FSEAT) and methanolic (SEM) extract of M. imbricata and tingenone presented antinociceptive activity in vivo when tested in mice, making them probable promising analgesics.